The educational value of the use of forms, methods and tools of interactive methods in the organization of primary school lessons through new pedagogical technologies - Mamatkulova Yulduz Sherozovna (Genius Journals, 2022)
This article analyzes the educational significance of the use of forms, methods and tools of interactive methods in the organization of primary school reading through new pedagogical technologies
Keywords: primary school; lesson; interactive method; state educational